The Analysis of Optimal Stock-Bond Portfolio Strategy: Empirical Study in LQ 45 Index Companies and Government Bonds Listed on Indonesia Stock Exchange - Yoga Yudha Pratama; Isni Andriana; H. M. A. Rasyid HS Umrie (Program Studi Magister Manajemen FE Unsri, 2020)
This study aims to analyze the strategy in determining the optimal stocks portfolio performance through Single Index Model technique from LQ 45 Index stocks and optimal bonds portfolio performance of bonds through Buy and Hold technique from government bonds in Indonesia Stock Exchange in the 2014-2018 period. The strategy generates performance which generally consists of optimal return (yield), risk and portfolio proportion. The population used in the study are companies stock in LQ 45 Index which produced 23 samples and government bonds produced 7 samples. The methodology research in this study is descriptive analysis. The type of data used in this study is quantitative and data sources of this study is secondary data. Purposive sampling method used as the sampling method. This research found that optimal stock portfolio performance with expected return and optimal portfolio risk values at 0.01497 and 0.006395 while optimal bonds portfolio performance showed optimal portfolio yields and risk with values at 0.090063991 and -0.003063991. The proportions of fund that invested in the optimal stock portfolio are BBCA (27%), GGRM (12%), TLKM (11%), ICBP (14%), PTBA (5%), UNVR (10%), BBRI (9%), BBNI (6%), BMRI (5%) and UNTR (2%) while the optimal bonds portofolio proportions are FR0073 (90%) and FR0072 (10%).